2009
DOI: 10.1016/j.exer.2008.07.018
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ promotes Wnt expression during cataract development

Abstract: TGFβ induces lens epithelial cells to undergo epithelial mesenchymal transition (EMT) and many changes with characteristics of fibrosis including posterior capsular opacification (PCO). Consequently much effort is directed at trying to block the damaging effects of TGFβ in the lens. To do this effectively it is important to know the key signaling pathways regulated by TGFβ that lead to EMT and PCO. Given that Wnt signaling is involved in TGFβ-induced EMT in other systems, this study set out to determine if Wnt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 41 publications
5
30
0
Order By: Relevance
“…In ocular fibrosis, Wnt has been shown to be activated by TGF-β1 during cataract development (Chong et al, 2009) and in human orbital fibroblasts to enhance ECM production (Tan et al, 2014). Wnt inhibition suppresses the TGF-β1 inducing effects in ECM synthesis (Tan et al, 2014) and protects against diabetic retinopathy in a mouse model of induced retinal ischemia (Park et al, 2011b).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…In ocular fibrosis, Wnt has been shown to be activated by TGF-β1 during cataract development (Chong et al, 2009) and in human orbital fibroblasts to enhance ECM production (Tan et al, 2014). Wnt inhibition suppresses the TGF-β1 inducing effects in ECM synthesis (Tan et al, 2014) and protects against diabetic retinopathy in a mouse model of induced retinal ischemia (Park et al, 2011b).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…Ono et al have demonstrated that the downregulation of WNT/β-catenin signaling, via inhibitor of β-catenin and TCF4 (ICAT), niclosamide, or XAV939, has antitumor effects on primary cultures of human leiomyoma cells in vitro [54]. TGFβ facilitates the translocation of un-phosphorylated β-catenin from the cytoplasm to the nucleus [55] and via integration with the T-cell factor and lymphoid enhancer factor-1 (TCF/LEF1) family of transcription factors to activate WNT target gene expression [56]. In our study, we found that fucoidan treatment decreased the levels of β-catenin in both the cytoplasm and the nucleus in ELT-3 cells and abolished the TGFβ3-induced β-catenin translocation into the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases the result is to promote transdifferentiation. A report using whole rat lens cultures exposed to TGFb2 and transgenic mice over expressing TGFb1 demonstrated increased level of Wnt ligands and Frizzled receptors compared with controls; moreover, this was associated with increased accumulation of b-catenin in the nucleus of cataract forming cells and expression of aSMA/plaque formation [99].…”
Section: Tgfb: the Orchestrator Of Fibrosismentioning
confidence: 99%